2012
DOI: 10.1155/2012/539412
|View full text |Cite
|
Sign up to set email alerts
|

The End-Organ Impairment in Liver Cirrhosis: Appointments for Critical Care

Abstract: Liver cirrhosis (LC) can lead to a clinical state of liver failure, which can exacerbate through the course of the disease. New therapies aimed to control the diverse etiologies are now more effective, although the disease may result in advanced stages of liver failure, where liver transplantation (LT) remains the most effective treatment. The extended lifespan of these patients and the extended possibilities of liver support devices make their admission to an intensive care unit (ICU) more probable. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 98 publications
(95 reference statements)
0
9
0
2
Order By: Relevance
“…recently demonstrated that EMR2 is a potential biomarker for SIRS and it is associated with the extent of organ failure26. Child C or decompensated end-stage liver disease often leads to multiple organ failure427. Although oxidative burst (production of reactive oxygen) of neutrophils is a major host defense mechanism to kill invading microorganisms, its excessive activities had been shown to be associated with SIRS and the extent of organ failure1828.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…recently demonstrated that EMR2 is a potential biomarker for SIRS and it is associated with the extent of organ failure26. Child C or decompensated end-stage liver disease often leads to multiple organ failure427. Although oxidative burst (production of reactive oxygen) of neutrophils is a major host defense mechanism to kill invading microorganisms, its excessive activities had been shown to be associated with SIRS and the extent of organ failure1828.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cirrhosis are susceptible to a variety of complications, and their life expectancy can be markedly reduced, especially in those with acute on chronic liver failures23. Infections, especially bacterial infections, account for the major causes for decompensating liver cirrhosis4 or acute on chronic liver failure, and contribute towards high morbidity and mortality of these patients56.…”
mentioning
confidence: 99%
“…This condition is defined as an advanced stage of progressive fibrosis of the liver that is identifiable by disruption of the lobular architecture and hepatic vasculature [2].…”
Section: Introductionmentioning
confidence: 99%
“… 100 The pathophysiological backgrounds of the responders to high-dose furosemide+HSS should be further cautiously investigated for adequate patient selection. While elevated serum BNP level is considered to reflect left ventricular myocardial dysfunction (impaired systolic function and/or diastolic relaxation), 101 103 an elevated serum ANP level is attributable to increased atrial volume or pressure. 101 , 103 , 104 The latter may reflect increased blood volume in liver cirrhosis (overflow state), 104 although a study by Tuttolomondo et al 99 did not concomitantly evaluate RAAS or SNS.…”
Section: Experimental Treatmentsmentioning
confidence: 99%